2023
DOI: 10.3389/feduc.2023.1139648
|View full text |Cite
|
Sign up to set email alerts
|

The scientific evolution of social justice leadership in education: structural and longitudinal analysis of the existing knowledge base, 2003–2022

Abstract: This study aims to delineate the intellectual and conceptual architecture of social justice leadership (SJL) research in education by reviewing the strategic themes that emerged during its scientific evolution. The study combines bibliometric performance and science mapping analysis of 135 articles on “SJL in education” retrieved from the Scopus database. SciMAT software (version 1.1.04) was used for the study since it allows for sequential analysis. Our analysis comprised three periods: Period 1 (2003–2012), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The results of this analysis can be used as a basis for developing inclusion and exclusion criteria in this bibliometric analysis. Inclusion criteria and exclusion criteria are used to determine the eligibility of articles, documents that are not appropriate will be excluded because they are considered outside the scope (Karakose et al, 2023). By doing so, we improved consistently the quality of research (Corsini et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The results of this analysis can be used as a basis for developing inclusion and exclusion criteria in this bibliometric analysis. Inclusion criteria and exclusion criteria are used to determine the eligibility of articles, documents that are not appropriate will be excluded because they are considered outside the scope (Karakose et al, 2023). By doing so, we improved consistently the quality of research (Corsini et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used bibliometric analysis to identify core articles, authors, countries, institutions, and journals in the research area of mobile learning adoption and continuance in education. In addition, an evaluation of the existing 155 relevant articles obtained from the WoS database revealed knowledge flows and evolving research themes [58]. Although the study is limited by reliance on a single research database, it offers multiple conclusions for MACE research.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research also called attention to the socio-economic status of students' families as a strong determinant of achievement gaps. This research provided evidence that principals' instructional leadership might help narrow the SES-based achievement gap by improving learning-related conditions in schools [138][139][140]. Shaked [133] suggested that principals' instructional leadership could eliminate injustices through school improvement 'because it strives rigorously to lead all students to high academic performance, regardless of diverse students' potentially marginalizing characteristics' (p.2).…”
Section: Period 4 (2020-2023)mentioning
confidence: 96%
“…Other subthemes associated with EDUCATIONAL-LEADERSHIP were Principal-Instructional-Leadership, School-Principalship, Democratic-Leadership, and Leadership-Preparation. A study by Karakose et al [138] found that research on social justice leadership increased significantly after 2018, and reached its peak in 2021. Researchers offered two explanations for increased interest in social justice leadership.…”
Section: Period 4 (2020-2023)mentioning
confidence: 99%